DIGITAL CONTENT ANALYSIS OF THE DEPARTMENT OF CULTURE, TOURISM AND CREATIVE ECONOMY OF NORTH SUMATERA PROVINCE FROM ROLAND BARTHES' SEMIOTIC PERSPECTIVE - Maruhawa, Tamara Khaisya; Deni, Indira Fatra (Journal Analytica Islamica, 2025)
This study aims to uncover layers of meaning in the digital content of the North Sumatra Disbudparekraf, in order to understand more deeply how visual communication strategies and digital narratives are utilized to shape public perceptions of cultural and creative economic development in North Sumatra. The theory used is Barthes' theory, such as myths, signification systems, and the relationship between signifiers and signifieds. This study uses a qualitative approach with Roland Barthes' semiotic analysis to examine the meaning in the digital content of the North Sumatra Disbudparekraf on Instagram and YouTube 2024. The analysis was carried out on the denotative and connotative meanings of visual elements and cultural symbols. Data were analyzed using visual content techniques and validated with theory triangulation. The results of the study show that visual symbols in government digital media not only convey information, but also play a role in forming modern myths that can influence public opinion and collective image. Thus, digital content has great potential as a tool for cultural diplomacy, tourism promotion, and strengthening local identity in a global context.